DETERMINING THE BRAND LOYALTY OF RICEBERRY PRODUCT IN YASOTHON OF THAILAND: MODERATING ROLE OF PERCEIVED QUALITY - Jermsittiparsert, Kittisak; Sriyakul, Thanaporn; Rattanasirivilai, Samanan; Horakul, Pissanu (RMUTT Global Business and Economics Review, 2022)
Brand loyalty is the positive feeling of the customer towards brand or product and customer repurchase and reuses it. In other words, it is called product addiction. Many related factors produce brand loyalty. The main aim of this study is to find out the different determinants of brand loyalty of Riceberry in Yasothon, Thailand with the moderation of perceived quality and value. Data is collected from the Rice industry in Yasothon, Thailand. Data is collected via the questionnaire by using e-mails of employees. The study is quantitative in nature and data is cross-sectional. After the collection of data, a statistical tool is applied to it. Results revealed that customer satisfaction, perceived quality, and value and preserves have a positive significant impact on brand loyalty of Riceberry. Moreover, perceived quality and value moderates the relation between customer satisfaction, preserves, and brand loyalty of Riceberry. This study suggested to managers of product companies of Riceberry that they have to focus on determinants like (customer satisfaction, perceived quality, and value and preserves) for increasing the brand loyalty of Riceberry.